Dasatinib-Induced Chylothorax in Chronic Myeloid Leukemia. Issue 1 (1st January 2017) - Baloch, Zulfiqar Qutrio; Abbas, Shabber Agha; Bhatti, Hammad; Braver, Yvonne; Ali, Sayed K.
Abstract : Pulmonary adverse events are common abnormalities associated with the use of dasatinib in chronic myeloid leukemia. We present a case of a 69-year-old man who suddenly developed a rare chylothorax pulmonary adverse event following 10 months of dasatinib treatment.